Developmental Impacts of PANS/PANDAS and Inadequate Support for Children and Families. - LaRusso, Maria D.; Abadía-Barrero, César (Child Psychiatry & Human Development, 2026)
This article examines the degree to which major domains of child development are affected by Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS)/Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS). Using cross-sectional survey data collected with an international sample of parents who identify as having children with PANS/PANDAS (N = 402), this study analyzed parent-reported developmental impacts and access to treatment and adequate supports. Parents reported that PANS/PANDAS negatively impacted their children's development across all domains: Emotional Development (92% of children), Social Development (90%), Cognitive Development (86%), Academic Growth (86%), Identity Development (83%), Talent Development (73%) and Language Development (50%). In addition, developmental impacts were likely to be more severe for children whose parents reported a greater number of inadequate supports with parenting, school, extracurricular activities, and crisis situations. These results indicate that children and families affected by PANS/PANDAS need better support to maximize children's opportunities, at home, in school, and in their communities, to continue developing despite challenging neuropsychiatric symptoms.